Hubungan Kecemasan dengan Prokrastinasi Akademik pada Mahasiswa Fakultas Psikologi Universitas Prima Indonesia - Siburian, Elizabeth Debora Debora; Wicaksana, Pramudya; Rezeki, Sabrini Mentari; Tarigan, Beby Astri (Universitas Syiah Kuala, 2025)
The study aims to examine the relationship between anxiety and academic procrastination in students of the Faculty of Psychology, Universitas Prima Indonesia. Using a quantitative correlational method. The population consists of 837 students of the Faculty of Psychology, Universitas Prima Indonesia with a sample size of 263 students selected using the disproportionate stratified random sampling technique. This study uses a quantitative method with data collection using an academic anxiety scale and an academic procrastination scale. The research data analysis test includes a normality test, a linearity test and data analysis in this study using Pearson product moment with the IBM SPSS Statistics 26 for Windows program. From the results of this study, a correlation of r = 0,221 and a significance of P = 0,000 (P 0,05) was obtained, so it can be concluded that the high and low levels of student anxiety at the Faculty of Psychology at Universitas Prima Indonesia have a unidirectional nature, which means that if the value of the dependent variable leads to an increase, then the independent variable will also have similar properties and vice versa.